2020
DOI: 10.1155/2020/3075429
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Major Causes of Calf Mortality in Urban and Periurban Dairy Production System of Ethiopia

Abstract: A cross-sectional calf mortality study was conducted in urban and periurban dairy farms in Addis Ababa, special zones of Oromia and Amhara regions in July and August 2015. e objectives of the study were to estimate the annual mortality and to assess the major causes of calf mortality in the dairy farms. One-year retrospective data on calf mortality were collected from 330 farms by face-to-face interview using the pretested and structured questionnaire format and direct observation of farm practices. A logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 12 publications
11
33
2
Order By: Relevance
“…Our findings revealed that abortion is widely prevalent in goat flocks compared to sheep flocks. The present study is consistent with previous studies in Ethiopia (22,31,33) and elsewhere (32). Almost all interviewed sheep and goat owners also confirmed the higher susceptibility of does to abortion than ewes.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings revealed that abortion is widely prevalent in goat flocks compared to sheep flocks. The present study is consistent with previous studies in Ethiopia (22,31,33) and elsewhere (32). Almost all interviewed sheep and goat owners also confirmed the higher susceptibility of does to abortion than ewes.…”
Section: Discussionsupporting
confidence: 94%
“…In contrary, a lower abortion rate has been reported from Jordan, 10.6% in does and 2.0% in ewes (33); from Nigerian, 10.8% in does (34) and from Mexico, 3.5% in does (35). Similarly, the higher abortion percentage in lowland flocks than in highland flocks is in agreement with the report of Gebremedhin et al (22) and Fentie (31) in Ethiopia. Mixed crop-livestock and pastoral production systems are practiced in dryland agro-ecosystems where multiple stressors such as the cumulative effects of poor nutrition, excessive heat, and the need to walk long distances to source feed and water compromise the production and reproduction performance of small ruminants (36).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Death during birth or shortly after birth was recorded in 12.8% of calves. High neonatal calf mortality was also observed in dairy farms by Fentie et al ( 24 ). High calf mortality was one of the major complaints of the farm owners in our study.…”
Section: Discussionmentioning
confidence: 59%
“…The most substantial savings were due to a decrease in requirements of bedding materials such as sawdust or wood shavings. Elsewhere, improved hygiene in calf pens as a result of housing upgrades had farreaching effects in optimizing growth and reducing disease and deaths (Fentie et al, 2020). Gitau et al (2010) identified gastrointestinal and respiratory conditions as a leading cause of calf mortality in the Nairobi peri-urban area, and suggested suitable housing as a possible remedy.…”
Section: Financial Analysismentioning
confidence: 99%